Impact of Voids on Mechanical Stability of Well Cement. (January 2016) - Lavrov, Alexandre; Todorovic, Jelena; Torsæter, Malin
Abstract: Techniques of well construction currently used in oil industry and for underground CO2 storage typically involve cementing a casing or liner in a borehole. Cement integrity affects the overall integrity of the well. Developing new sealing materials and predicting long-term integrity of CO2 injection wells requires a good understanding of defects in well cement, and how these defects may affect the well integrity. In this paper, voids and channels are observed in the cement near different cement-steel interfaces using a scanning electron microscope (SEM). The effect of voids on the stress state under mechanical or thermal loading of the near-well area is assessed numerically using a finite-element model of the casing-cement-rock system.